Compact RF/ Laser Dielectric Linacs for Internal and External Cancer Therapy and Dynamic DNA Damage/Repair Analysis - M. Uesaka; M. Pohl; K. Miyoshi; Y. Inoue; T. Takahashi; M. Ozeki; S. Kamei; J. Jang; M. Yoshida; K. Koyama; et al. (Recent Developments in Engineering Research Vol. 12, 2021)
We are performing three-staged development of compact linear accelerators (hereafter linac) with S-band (2.856 GHz, wavelength 105 mm), X-band (9.3 GHz, 32.3 mm) RF (Radio frequency) and Yb fiber laser (283 THz, wavelength 1.06 mm). Recently, we have proposed S-band 40 MeV 40 kW linac for Medical RI (Radioisotope) production of 99Mo/99mTc (g-emitter), 67Cu (b+) and 225Ac (a). X-band 6 MeV linac have been made for pinpoint X-ray dynamic tracking cancer therapy. The electron beam size at the X-ray target is less than 1 mm and X-ray spot size at the cancer is less than 3 mm. Several hardware and software are under construction for dynamic tracking Radiation Therapy (RT) for moving lung cancer. Moreover, as an ultimate compact linac, we are designing and manufacturing a laser dielectric linac of 1 MeV with Yb fiber laser. Since the wavelength is 1.06 mm, the length of one accelerating structure is tens mm and the electron beam size is 1mm. We plan to use this “On-chip” linac for radiation-induced DNA damage/repair analysis since the sizes of cell and nucleus are about 10 and 1 mm, respectively. We are thinking a system where DNA in a cell nucleus is hit by 1 mm electron- and ion-beams and observe its repair by proteins and enzymes in live cells in-situ. Finally, we try to contribute to advanced radiation biological research for theranostics (= therapeutics and diagnostics).